Through-focus performance and off-axis effects in aspheric monofocal intraocular lenses - Łabuz, Grzegorz; Yan, Weijia; Khoramnia, Ramin; Auffarth, Gerd U. (Biomedical optics express, 2024)
This study aimed to determine the through-focus performance and the effect of misalignment on the optical quality of different aspheric monofocal intraocular lenses (IOLs). To this end, optical quality was assessed in three IOL models with different optic surfaces: standard aberration neutral model and two spherical aberration (SA) correcting, one of which utilizes higher-order aspheric terms. The optical quality was measured by means of the modulation transfer function at 3- and 4.5-mm pupils and under monochromatic and polychromatic light with different corneal SA. The optically derived range of vision and tolerance to misalignment were also tested. The study demonstrated that the type of IOL surface affects the monofocal implant's performance. Although a standard primary-SA correction may improve scotopic image quality, misalignment may diminish this advantage. The higher-order aspheric surface used to correct SA provided an improved performance against decentration and offered a higher optical quality than the aberration-neutral design when tested in a model eye. The latter, however, demonstrated a high tolerance to misalignment, offering a slight extension of the range of vision, potentially resulting from uncorrected optical aberrations.